Pionnier de la Résistance Le réseau Grenier-Godard (1940-1942) - Vouzelle, Dimitri (Histoires, 2022)
The occupation of Dijon began on 17 June 1940. Very rapidly, numerous Dijon residents initiated the first protest against the defeat, including a family of the Saint-Michel district known as the Grenier-Godards: Alphonse, a soldier during World War I, gassed on the eastern front in 1917; Blanche, a nurse who became involved in September 1939; and their two young sons, René, fifteen, and Jean, eleven. Blanche, who organised the network, instigated secret activities: prisoner escapes, false IDs, crossing the demarcation line, secret services, and helping Jews. The network counted more than 300 members in 1942. A woman, a family, a district. How and why did the French enter the Resistance in the summer of 1940? How did a secret organisation operate at the beginning of this movement? Why was the Grenier-Godard network forgotten after being honoured and rewarded? These are the questions this monograph addresses so that the Dijon network can be rescued from the oblivion of history.